2013
DOI: 10.1186/1297-9716-44-41
|View full text |Cite
|
Sign up to set email alerts
|

The 2009 pandemic (H1N1) viruses isolated from pigs show enhanced pathogenicity in mice

Abstract: Since the emergence of the 2009 pandemic (H1N1) virus (2009/H1N1) in April 2009, cases of transmission from humans to pigs have been reported frequently. In our previous studies, four 2009/H1N1 variants were isolated from pigs. To better understand the phenotypic differences of the pig isolates compared with the human isolate, in this study mice were inoculated intranasally with different 2009/H1N1 viruses, and monitored for morbidity, mortality, and viral replication, cytokine production and pathological chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In this study, we assessed the pathogenicity and transmissibility of classic H3N2 virus strains (Chinese CIV JS/10, Korean CIV KR/07 and reassortant CIV MV/12) under the same conditions. Because the pathogenesis of the pandemic H1N1 CA/09 strain has been well addressed in animal models, including mice [ 19 , 31 ] and guinea pigs [ 32 ], we used this viral strain as a reference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we assessed the pathogenicity and transmissibility of classic H3N2 virus strains (Chinese CIV JS/10, Korean CIV KR/07 and reassortant CIV MV/12) under the same conditions. Because the pathogenesis of the pandemic H1N1 CA/09 strain has been well addressed in animal models, including mice [ 19 , 31 ] and guinea pigs [ 32 ], we used this viral strain as a reference.…”
Section: Discussionmentioning
confidence: 99%
“…Mice have shown promising potential for underlying the basic viral pathogenesis of influenza virus, which have traditionally been used as a mammalian animal model [ 5 , 18 , 19 ]. Alternatively, guinea pigs have also been reported to be a relevant model of influenza virus infection and are suitable for evaluations of the transmissibility of IAVs in mammalian hosts [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…BALB/c mice, these animals fits evaluation of immune response after baculovirus immunization and has suitable sensibility for mouse adapted pH1N1 virus [ 22 25 ]. For these purposes, we selected BALB/c mice to enhance the immunogenicity and reduce the antigen dose or immunization frequency required for protective immunity, we constructed a baculovirus vector carrying Mus musculus GmCSF (AcHERV-GmCSF) and tested its molecular adjuvant efficacy with killed—pH1N1 influenza—vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were few studies underlying the interactions of Sus scrofa (ssc-, swine) miRNAs and swine influenza viruses. In 2010, our lab isolated a pandemic H1N1/2009 influenza A virus in swine herds [ 17 ], and the next work demonstrated that this swine influenza virus possessed enhanced pathogenicity in mice [ 37 ]. In order to explore swine miRNAs that could regulate the SIV-H1N1/2009 replication, we predicted potential miRNAs targeting the viral genomic RNA by bioinformatics method, and identified ssc-miR-204 and ssc-miR-4331 as negative regulators of SIV-H1N1/2009 replication by targeting viral HA and NS respectively.…”
Section: Introductionmentioning
confidence: 99%